Case Report: Culture-Dependent Postures in Japanese Patients With Schizophrenia - Koreki, Akihiro; Koizumi, Teruki; Ogyu, Kamiyu; Onaya, Mitsumoto (Frontiers in Psychiatry, 2021)
Cross-cultural understanding of psychiatric symptoms is important in the current globalised society. Lack of knowledge regarding culture-dependent manifestations of psychiatric illnesses may lead to misjudgement by clinicians, resulting in inappropriate treatment. We present the cases of two patients with schizophrenia who showed Japanese-culture-dependent postures (seiza and dogeza). Seiza is a Japanese style of formal floor sitting. Dogeza includes bowing and touching the forehead to the floor while sitting in a kneeling position. When patients with schizophrenia perform these postures in a clinical setting, clinicians receive plenty of information regarding the patients' clinical states, including schizophrenia-related fear/tension, accusatory auditory verbal hallucinations, and pathological guilt.